Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.5251/ajsir.2011.2.4.678.685
|View full text |Cite
|
Sign up to set email alerts
|

A biomechanical model via Kane’s equation – solving trunk motion with load carriage

Abstract: Carrying a heavy backpack has become a phenomenon among school children and adults. A review of the literature on the effect of carrying backpack loads on the trunk backward and forward lean in children and adults showed that with a load of even less than 15% of body weight, children have to walk with a forward lean of the trunk, whereas adults are in a forward lean position only with a backpack loads of more than 27% of their body weight. Due to these biomechanical studies, a mathematical model of the upper b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Average height, mass and BMI were typical of 7-year-old children. The shift of center of gravity while the subjects were encumbered with a schoolbag was tested, and the anterior shift concurs with the results of many other studies [30,31,32,33] which measured the anterior shift of the torso in a standing position or during bipedal locomotion. Since the anterior shift of center of gravity while under a load in the form of a schoolbag is a well-known fact, the primary goal of this study was to measure the extent of the shift.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Average height, mass and BMI were typical of 7-year-old children. The shift of center of gravity while the subjects were encumbered with a schoolbag was tested, and the anterior shift concurs with the results of many other studies [30,31,32,33] which measured the anterior shift of the torso in a standing position or during bipedal locomotion. Since the anterior shift of center of gravity while under a load in the form of a schoolbag is a well-known fact, the primary goal of this study was to measure the extent of the shift.…”
Section: Discussionsupporting
confidence: 83%
“…The age difference could explain different findings because older children could have better postural control, even though they were carrying a heavier load. For example, one study [32] reviewed literature on trunk backward and forward lean and found that younger children had more pronounced lean forward than older children when encumbered with the same load ratio relative to the child’s mass. The authors hypothesized that an undeveloped musculoskeletal system was more prone to postural compensations when encumbered to better regain balanced position (center of gravity above center of base of support).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Kane's method has also been used to solve the problem of shoulder injury when planting palm oil [29]. Additionally, [30,31] have applied Kane's method for the construction of mathematical models for lifting activities as well as the effects of heavy lifting towards the spine. This shows that many activities have been improved to prevent injuries through mathematical modelling by using Kane's method.…”
Section: Introductionmentioning
confidence: 99%